Innovative Method for Remotely Fine-Tuning Offsets Along a Diverging Diamond Interchange Corridor. Issue 1 (2016) - Kim, SangKey; Warchol, Shannon; Schroeder, Bastian J.; Cunningham, Christopher
Diverging diamond interchanges (DDIs) are relatively new in the United States, and signal coordination between the crossovers and adjacent intersections is challenging. This paper provides a method for remotely fine-tuning offsets for a DDI and its adjacent intersections. The proposed method uses the dynamic bandwidth analysis tool (DBAT). The tool uses actuated phase times from the signal controller to optimize the dynamic bandwidth on the basis of that entry data set. Four performance measures evaluated the proposed method: delay, stop severity index, maximum queue, and vehicle trajectory plots. The test results confirmed that DBAT provided a better offset solution than other bandwidth optimization tools that generally optimized programmed bandwidth only and did not account for early return to green caused by skipped or gapped-out movements. Under the DBAT offsets, delay for the through movements on the corridor decreased by 52.8% for northbound vehicles and 46.83% for southbound vehicles. The average delay reduction over all measured paths for uncongested and congested scenarios was 13.88% and 3.50%, respectively. The proposed method and workflow can significantly reduce the offset retiming work process. Normally, this manual process takes more than a day, but the proposed method can be completed in less than an hour without visiting the study site. Furthermore, the proposed method can coordinate any set of movements, as well as multiple travel paths. The authors believe that the proposed method and workflow will significantly help both retiming and new timing of arterial signal coordination along DDI corridors and other signal systems.